Architectural Design of Business Processes For Community Empowerment and Flexibility Based on Presidential Regulation Number 132 of 2022 - Farida, Farida; Firmansyah, Gerry (Journal Research of Social Science, Economics, and Management, 2023)
The development of information technology in daily life is very rapid so that it can increase the productivity of an individual or organization. The Government Sector also utilizes information technology in an effort to increase the provision of effective and efficient public services. Likewise with the Government of Indonesia, in 2018 issued Presidential Regulation No. 95 of 2018 concerning Electronic-Based Government Systems (SPBE) as a guideline for governance that utilizes information and communication technology to provide quality public services. SPBE evaluation and monitoring is carried out by the Ministry of State Apparatus Empowerment and Bureaucratic Reform (KemenPANRB) in every government agency in Indonesia. In 2020 the results of the SPBE evaluation at the Tangerang City Government obtained a score of 3.44 with a good index. For this reason, this research focuses on improving SPBE governance which includes the standardization and integration of SPBE business processes for the Tangerang City Government. This research provides a solution in the form of an SPBE enterprise architecture design in the business process domain according to the SPBE architecture. Several phases are used, namely the preliminary phase, architecture vision, and business process architecture. The main phase of this design is the business process architecture which produces level 0 business process maps, level 1, 2, 3, 4, 5 business process maps and cross-functional maps as standardization of SPBE business processes according to PermenPANRB No. 19 of 2018.